Controlador óptimo de tiempo mínimo para un motor DC controlado en posición - Melgarejo Rey, Miguel Alberto; Pirajan Aranguren, Alexis Javier; Valdés, Cesar Augusto (Ingeniería, 2000)
This article presents the modeling and realization of a minimum time optimal controller for a position controlled DC motor. Controller architecture is implemented using a codesign approach where a CPLD (Complex Programmable Logic Device) is used as a signal adjustment system, and the control structures are high level specified virtual models.Controller functionality is verified comparing some transient responses of the control system under simulation and real work operation.